PENGENDALIAN RUMAH PINTAR MENGGUNAKAN JARINGAN INTERNET BERBASIS RASPBERRY PI - Bobby Risaldo Agung Putra; Erfan Rohadi; Rudy Ariyanto (SENTIA 2016, 2016)
A lot of workers have a hectic schedule. They have so many business negotiations and moreover the job is in out of the city they living. Based on the bustle job, it makes the workers do not stay in the house for a long time. Many effects may impact on the house, like thief and power management. Raspberry Pi is a mini computer which is the main device that can be used to control electronic equipments in the house. This controlling can be activated from anywhere, as long as the area has an internet connection, even the IP Address has the same network or not. By using Forward Chaining method, the control does not need to be done manually. This method can control electronic devices that are in the house automatically, using existing facts on the knowledge base. The controlling can be done by a website which can be accessed through smartphones or personal computers. The results of this research can be implemented at houses, schools, offices, from small scale to medium. This system is expected to prevent anything undesirable but can saving more energy significantly.